Linked Open Data and Medieval Studies: Some Lessons from the Mapping Manuscript Migrations Project. Issue 1 (March 2022) - Burrows, Toby
Abstract : Building on the work of the Mapping Manuscript Migrations (MMM) Project between 2017 and 2020, this article aims to identify the potential benefits and likely challenges of using Linked Open Data (LOD) more widely across the research field of medieval studies. As well as aggregating and linking disparate datasets relating to the history of more than 220, 000 medieval manuscripts, the MMM Project reconciled and matched vocabularies for places, persons, organizations, works and manuscripts. It built and tested various forms of access to the aggregated data, including a web portal and a SPARQL endpoint. It also demonstrated suitable ways of publishing its outputs, not only the aggregated data but also the data model and ontologies used. Drawing on the lessons learned in the MMM Project, the article offers suggestions for building an LOD environment for Western European medieval studies more broadly, covering the aggregation of heterogeneous data, the reconciliation of disparate vocabularies, and ways of enabling more effective discovery, exploration and analysis across the aggregated data.